2023
DOI: 10.3390/su15097580
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Surrogate Safety Measures Uses in Historical Crash Investigations

Abstract: Historical road crash data are the main indicator for measuring road safety outcomes. Over the past few decades, significant efforts have been made in obtaining and exploiting Surrogate Safety Measures (SSMs). SSMs have the potential to provide excellent sustainable road safety indicators and proxy measurements which can complement traditional historical crash analyses or even substitute them. By using SSMs, crash data collection demands can be bypassed and areas can be investigated before crashes occur. Due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 92 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…However, the paper investigates only the possible occurrence of motorway rear-end collisions. SSMs studies demonstrated an increasing research interest in the last years, as demonstrated also by the review article from Nikolaou et al [ 83 ].…”
Section: Resultsmentioning
confidence: 92%
“…However, the paper investigates only the possible occurrence of motorway rear-end collisions. SSMs studies demonstrated an increasing research interest in the last years, as demonstrated also by the review article from Nikolaou et al [ 83 ].…”
Section: Resultsmentioning
confidence: 92%
“…A useful conclusion that can be drawn on this basis has to do with the fact that the harsh acceleration related variable does not make a significant contribution to the prediction of the segment crash risk level. Based on the literature, both harsh accelerations and harsh brakings constitute Surrogate Safety Measures that can be used in various road safety analyses [33][34][35][36]. However, the results of this investigation suggest that harsh brakings may be more pertinent than harsh accelerations for predicting the crash risk level of motorway segments overall.…”
Section: Resultsmentioning
confidence: 93%
“…It is worth noting that Figure 2 shows the c tribution of only a subset of the variables that have been included in the multiclass cla fication RF model, as the other variables are not contributing much to the model's pre tions and their contribution to the model's output can be, therefore, considered negligi A useful conclusion that can be drawn on this basis has to do with the fact that the ha acceleration related variable does not make a significant contribution to the predictio the segment crash risk level. Based on the literature, both harsh accelerations and ha brakings constitute Surrogate Safety Measures that can be used in various road sa analyses [33][34][35][36]. However, the results of this investigation suggest that harsh braki may be more pertinent than harsh accelerations for predicting the crash risk level of Finally, a similar approach could be applied to a motorway segment with different characteristics from the representative motorway presented, in order to investigate the respective contribution of each feature to the model's prediction for each class.…”
Section: Resultsmentioning
confidence: 99%